THE BARRIER FACTORS OF ONLINE LEARNING IN LEARNING ENGLISH LANGUAGE SKILLS IN FOURTH SEMESTERS STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM - Putri Utami, Mira; Andriani, Reni; Fitria, Wahyuni (JR-ELT (Journal of Research in English Language Teaching), 2022)
The main purpose of this study was to find out the barrier factors of learning process in fourth semester students in learning English skills through online learning method in English Education Study Program at UIN STS Jambi. A case study was used in the design of this study. The subjects of this study were students of the fourth semester of English Education Study Program. This research data was collected through observation and interview, based on findings and analysis, the process of learning English skills by students of the fourth semester of the English Education Study Program through online learning has several barrier factors. One of these factors is the lack of facilities and infrastructure in the learning process using online learning methods. In addition, the lack of facilities of the students is also the cause of barrier on the learning process using online learning methods. Moreover, the lack of parental cooperation in the learning process is also a factor. This happened due to the differences students’ learning method with their parent. Meanwhile, the implementation of online learning methods cannot be applied as a whole well. This is indicated by the method of online learning is more dominant and obstacles appeared when teaching and learning process in the fourth semester students of English Education Study Program.